The Nordic Obstetric Surveillance Study: A Study of Complete Uterine Rupture, Abnormally Invasive Placenta, Peripartum Hysterectomy, and Severe Blood Loss at Delivery. Issue 2 (June 2016) - Colmorn, L.B.; Petersen, K.B.; Jakobsson, M.; Lindqvist, P.G.; Klungsoyr, K.; Källen, K.; Bjarnadottir, R.I.; Tapper, A.M.; Børdahl, P.E.; Gottvall, K.; Thurn, L.; Gissler, M.; et al.
Abstract : ( Acta Obstet Gynecol Scand . 2015;94:734–744) There is a lack of reliable research regarding severe complications at delivery, which is most likely due to the rarity of such complications. There is also the issue of interactions between different severe complications, questionable reporting, and the absence of precise terminology. The Nordic Obstetric Surveillance Study (NOSS) evaluated the rate of uterine rupture, placenta accreta, peripartum hysterectomy, and severe blood loss during delivery in Nordic countries as well as the characteristics of the women who suffered these complications. The aim was to provide valuable information that might help guide the management of obstetric emergencies.